The complex photochemistry of coumarin-3-carboxylic acid in acetonitrile and methanol - Yang, Qiuyun; Váňa, Jiří; Klán, Petr (Springer Nature Switzerland AG, 2022)
Irradiation of coumarin-3-carboxylic acid in acetonitrile and methanol solutions at 355 nm results in complex multistep photochemical transformations, strongly dependent on the solvent properties and oxygen content. A number of reaction intermediates, which themselves undergo further (photo)chemical reactions, were identified by steady-state and transient absorption spectroscopy, mass spectrometry, and NMR and product analyses. The triplet excited compound in acetonitrile undergoes decarboxylation to give a 3-coumarinyl radical that traps molecular oxygen to form 3-hydroxycoumarin as the major but chemically reactive intermediate. This compound is oxygenated by singlet oxygen, produced by coumarin-3-carboxylic acid sensitization, followed by a pyrone ring-opening reaction to give an oxalic acid derivative. The subsequent steps lead to the production of salicylaldehyde, carbon monoxide, and carbon dioxide as the final products. When 3-coumarinyl radical is not trapped by oxygen in degassed acetonitrile, it abstracts hydrogen from the solvent and undergoes triplet-sensitized [2 + 2] cycloaddition. The reaction of 3-coumarinyl radical with oxygen is largely suppressed in aerated methanol as a better H-atom donor, and coumarin is obtained as the primary product in good yields. Because coumarin derivatives are used in many photophysical and photochemical applications, this work provides detailed and sometimes surprising insights into their complex phototransformations.
Komplexní fotochemie kumarin-3-karboxylové kyseliny v acetonitrilu a methanolu
Keywords: photochemistry; coumarin; photooxidation; singlet oxygen; fotochemie; kumarin; fotooxidace; singletový kyslík